Comparative analysis of pathogenicity and anticoccidial resistance of field-isolated Eimeria strains in Sichuan Province, China - Zhang, Runhui; Li, Haitao; Wang, Xiao; Jike, Rihong; Lu, Shuaiqian; Hao, Lili (Frontiers in Veterinary Science, 2026)
Chicken coccidiosis is an intestinal protozoan disease caused by Eimeria, which is distributed worldwide and causes significant economic losses in the poultry industry. Owing to prolonged anticoccidial use, drug resistance has become an important obstacle to the control of coccidiosis. This study aimed to evaluate the pathogenicity of three mixed-species Eimeria isolates collected from chicken farms in Sichuan Province, China. The drug resistance of the isolates was also evaluated, including synthetic drugs, ionophores, and a natural herb. A total of 132 newborn chicks were grouped, including an infected-treated group, a positive control for each isolate, and a negative control. Survival rate, weight gain, oocyst excretion, and lesion scores were recorded. The pathogenicity and drug resistance of the three isolates were determined by four indices, including the anticoccidial index (ACI), the optimal percentage of anticoccidial activity (POAA), the relative oocyst production (ROP), and the reduction of lesion score (RLS). The results showed that only one Eimeria spp. isolated from Xichang was sensitive to sulfaclozine, whereas the rest of the isolates exhibited resistance to all tested drugs, with most isolates demonstrating severe or complete resistance. These findings are crucial for the selection of a regional drug administration program to control coccidiosis in chickens.